(untitled) (Bangladesh Journal of Pharmacology, 2023)
The objectives of the present study were to evaluate the antioxidant and anti-inflammatory effects of gallic acid, a naturally occurring triphenolic compound, on HaCaT keratinocytes and study its mechanisms of action. The results showed that gallic acid at concentrations lower than 30 µM was non-toxic to HaCaT cells, reduced the intracellular level of reactive oxygen species, and suppressed the release of chemokines interleukin-8 and monocyte chemoattractant protein-1 in tumor necrosis factor-α- and interferon-γ-stimulated HaCaT keratinocytes. In addition, gallic acid reduced the total protein expression of NF-κB and inhibited the phosphorylation of ERK1/2, p38 MAPK, and Akt in stimulated HaCaT keratinocytes. In conclusion, our study revealed that gallic acid exhibited antioxidant and anti-inflammatory effects on keratinocytes, probably through the inhibition of MAPK-, NF-κB-, and Akt-dependent signaling pathways.